The effectiveness of video animations as information tools for patients and the general public: A systematic review - Moe-Byrne, Thirimon; Evans, Ella; Benhebil, Nadia; Knapp, Peter (Frontiers in Digital Health, 2022)
Background & objectives: Video animations are used increasingly as patient information tools; however, we do not know their added value compared to other formats of delivery, such as printed materials, verbal consultations or static images. Methods: This review compares the effectiveness of video animations as information tools versus other formats of delivery on patient knowledge, attitudes and cognitions, and behaviours. Included studies had the following features: controlled design with random or quasi-random allocation; patients being informed about any health condition or members of the public being informed about a public health topic; comparing video animation with another delivery format; animation delivered either instead of, and behaviours. Multiple digital databases were searched from 1996-June 2021. We also undertook citation searching. We used dual, independent decision-making for inclusion assessment, data extraction and quality appraisal. Included studies were appraised using the Cochrane ROB2 tool. Findings were reported using narrative synthesis. Results: We included 38 trials, focussed on: explaining medical or surgical procedures (n=17); management of long-term conditions (n=11); public health, health-promotion or illness-prevention (n=10). Studies evaluated cartoon animations (n=29), 3D animations (n=6), or 2D animations, ‘white-board’ animations or avatars (n=1 each). Knowledge was assessed in 28 studies, showing greater knowledge from animations in 19 studies, compared to a range of comparators. Attitudes and cognitions were assessed in 21 studies, and animations resulted in positive outcomes in six studies, null effects in 14 studies, and less positive outcomes than standard care in one study. Patient behaviours were assessed in nine studies, with animations resulting in positive outcomes in four and null effects in the remainder. Overall risk of bias was ‘high’ (n=18), ‘some concerns’ (n=16) or ‘low’ (n=4). Common reasons for increased risk of bias were randomisation processes, small sample size or lack of sample size calculation, missing outcome data, and lack of protocol publication. Discussion: The overall evidence base is highly variable, with mostly small trials. Video animations show promise as patient information tools, particularly for effects on knowledge, but further evaluation is needed in higher quality studies.